Prolonged Blood Storage and Risk of Posttransfusion Acute Kidney Injury. (January 2022) - Adegboye, Janet; Sapatnekar, Suneeti; Mascha, Edward J.; Shah, Karan; Lioudis, Michael; Essber, Hani; Cohen, Barak; Rivas, Eva; Heddle, Nancy M.; Eikelboom, John W.; Ellis, Martin H.; Sharon, Yehudit; et al.
Abstract : Background: Erythrocyte transfusions are independently associated with acute kidney injury. Kidney injury may be consequent to the progressive hematologic changes that develop during storage. This study therefore tested the hypothesis that prolonged erythrocyte storage increases posttransfusion acute kidney injury. Methods: The Informing Fresh versus Old Red Cell Management (INFORM) trial randomized 31, 497 patients to receive either the freshest or oldest available matching erythrocyte units and showed comparable mortality with both. This a priori substudy compared the incidence of posttransfusion acute kidney injury in the randomized groups. Acute kidney injury was defined by the creatinine component of the Kidney Disease: Improving Global Outcomes criteria. Results: The 14, 461 patients included in this substudy received 40, 077 erythrocyte units. For patients who received more than one unit, the mean age of the blood units was used as the exposure. The median of the mean age of blood units transfused per patient was 11 days [interquartile range, 8, 15] in the freshest available blood group and 23 days [interquartile range, 17, 30] in the oldest available blood group. In the primary analysis, posttransfusion acute kidney injury was observed in 688 of 4, 777 (14.4%) patients given the freshest available blood and 1, 487 of 9, 684 (15.4%) patients given the oldest available blood, with an estimated relative risk (95% CI) of 0.94 (0.86 to 1.02; P = 0.132). The secondary analysis treated blood age as a continuous variable (defined as duration of storage in days), with an estimated relative risk (95% CI) of 1.00 (0.96 to 1.04; P = 0.978) for a 10-day increase in the mean age of erythrocyte units. Conclusions: In a population of patients without severely impaired baseline renal function receiving fewer than 10 erythrocyte units, duration of blood storage had no effect on the incidence of posttransfusion acute kidney injury. Abstract : In a planned subanalysis of a large trial that evaluated mortality in hospitalized patients randomized to either the freshest or the oldest available erythrocyte units, there was no difference in the incidence of posttransfusion acute kidney injury.